2022
DOI: 10.3389/fphys.2022.812157
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Senescent Bone Cells and the Bone Tissue Microenvironment Influences Bone Fragility During Chronological Age and in Diabetes

Abstract: Bone is a complex organ serving roles in skeletal support and movement, and is a source of blood cells including adaptive and innate immune cells. Structural and functional integrity is maintained through a balance between bone synthesis and bone degradation, dependent in part on mechanical loading but also on signaling and influences of the tissue microenvironment. Bone structure and the extracellular bone milieu change with age, predisposing to osteoporosis and increased fracture risk, and this is exacerbate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 247 publications
0
9
0
Order By: Relevance
“…Research has found that bone can not only support the body and protect organs but also can be considered an immune organ 3,4 . At the beginning of the 21st century, the concept of “osteoimmunology” was proposed by Arron, which elaborated on the relationship between the immune system and bone.…”
Section: Concept Of Osteoimmunologymentioning
confidence: 99%
“…Research has found that bone can not only support the body and protect organs but also can be considered an immune organ 3,4 . At the beginning of the 21st century, the concept of “osteoimmunology” was proposed by Arron, which elaborated on the relationship between the immune system and bone.…”
Section: Concept Of Osteoimmunologymentioning
confidence: 99%
“…Moreover, age-related bone degradation is accelerated by accumulation of senescent bone cells ( Kassem and Marie, 2011 ). Cellular senescence is a natural process in which cells lose their ability to divide and remain as viable but functionally altered cells, and is triggered by stressors including DNA damage, oncogene activation and inflammatory signals ( Teissier et al, 2022b ). Senescent cells in turn produce inflammatory markers to induce a cycle of bone remodeling, and can induce senescence in neighbouring cells.…”
Section: Pathophysiology Of Osteoporosismentioning
confidence: 99%
“…Importantly, this bone microenvironment is the primary repository of calcium, which is incorporated and mobilized from the osteoid matrix to respond to systemic demand (reviewed in Murshed, 2018; Tresguerres et al, 2020). Factors like race (Noel et al, 2021), age (I.O.F., 2022; Veldurthy et al, 2016), and concomitant morbidities like diabetes (Ahn et al, 2017; Cipriani et al, 2020; Jackson and Moseley, 2020; Teissier et al, 2022) impact bone calcium homeostasis: they can result in osteopenia (loss of calcified bone mineral density) and osteoporosis (loss of mineral density that results in decreased bone strength). Adding complexity to these phenotypes, the standard of care for prostate cancer also negatively impacts bone matrix integrity.…”
Section: Introductionmentioning
confidence: 99%